Day 4 Thu, June 15, 2017 2017
DOI: 10.2118/185856-ms
|View full text |Cite
|
Sign up to set email alerts
|

Representative Sector Modeling and Key Factors Impact on Waterflooding Performance of a Large Multi-Layered Sandstone Reservoir

Abstract: M1 reservoir is a large multi-layered sandstone reservoir of deltaic environment with oil bearing area more than 500Km2. And M1 is influenced by fluvial, tide and wave, which results in great variations of sand bodies’ distribution, reservoir quality and connectivity. So it is essential to use high resolution models capturing reservoir heterogeneity for this kind of reservoirs. This paper presents an approach to representative sector modeling and key factor impact on waterflooding performance study for a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Depending on the well logs response and final well report (FWR), FZI values were distributed among the reservoir major units, where the unit with good properties has taken a higher FZI value and so on. Based on these subdivisions, the permeability value was obtained using equation (2)(3)(4)(5) and FZI values were specified for each subunit. Figure-3 shows the plot of core and predicted permeability versus depth, which gives an acceptable agreement between core permeability and K-calculated from FZI approach.…”
Section: -1mentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the well logs response and final well report (FWR), FZI values were distributed among the reservoir major units, where the unit with good properties has taken a higher FZI value and so on. Based on these subdivisions, the permeability value was obtained using equation (2)(3)(4)(5) and FZI values were specified for each subunit. Figure-3 shows the plot of core and predicted permeability versus depth, which gives an acceptable agreement between core permeability and K-calculated from FZI approach.…”
Section: -1mentioning
confidence: 99%
“…Sector modeling is more convenient to represent a comprehensive field and can accelerate reservoir simulations and characterizations by focusing on the sector only. This helps to construct both geological and dynamic models quickly and easily [5,6].…”
Section: -Introductionmentioning
confidence: 99%
“…If a formation comprising several layers with diff erent permeability is involved in the process, water mainly fi lls thick zones with higher permeability, without entering thin zones where the permeability is much lower. It has been observed that the permeability of the zones increases as the water passing through them pushes the oil out [13,14].…”
mentioning
confidence: 99%